Rare metastatic pancreatic tumors from lung cancer with cystic changes resembling intraductal papillary mucinous neoplasm: a case report - Akira Watanabe; Norifumi Harimoto; Takahiro Yamanaka; Norihiro Ishii; Mariko Tsukagoshi; Takamichi Igarashi; Norio Kubo; Kenichiro Araki; Aya Suzuki; Kenichiro Hara; Ken Shirabe (Surgical Case Reports, 2020)
Abstract Background Metastatic pancreatic tumors from lung cancer (MPTLC) constitute 3% of all metastatic pancreatic tumors. We present an extremely rare case of cystic MPTLC that was difficult to distinguish from intraductal papillary mucinous neoplasm (IPMN). Case presentation The patient was a 74-year-old woman who underwent lobectomy of lung cancer 2 years before presentation to our hospital. She was referred to our department for resection of cystic pancreatic tumors, which were diagnosed as IPMN with high-risk stigmata. Abdominal computed tomography (CT) showed a 37-mm-wide cystic tumor with a contrasted solid nodule in the pancreatic head and a 17-mm-wide cystic tumor in the pancreatic tail. We performed a total pancreatectomy for these lesions. According to histopathological and immunohistochemical findings, the tumors were diagnosed as metastatic pancreatic tumors from lung cancer. Conclusion In this case, the cystic morphology was formed by eosinophilic secretions from tumor cells, and it was difficult to distinguish from IPMN with high-risk stigmata. We consider this case, based on the variable clinical findings, an extremely rare variant of MPTLC.